2016
DOI: 10.3852/15-175
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization, sexual reproduction, and pathogenicity ofSetosphaeria rostrataisolates from rice leaf spot

Abstract: Setosphaeria rostrata, a common plant pathogen causing leaf spot disease, affects a wide range of plant species, mainly grasses. Fungi were isolated from brown spots on rice leaves throughout Peninsular Malaysia, and 45 isolates were identified as Setosphaeria rostrata The isolates were then characterized using morphological and molecular approaches. The mating type was determined using PCR amplification of the mating type alleles, and isolates of opposite mating types were crossed to examine sexual reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In contrast to B. oryzae populations, E. rostratum populations showed a dominant distribution of a single mating type, MAT1-2 (79%). These results are similar to those of Kusai et al (2016), observed on E. rostratum isolates from rice in Malaysia. The linkage disequilibrium and homoplasy tests did not reject the hypothesis of recombination within the E. rostratum populations of Burkina Faso.…”
Section: Rodolfisupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to B. oryzae populations, E. rostratum populations showed a dominant distribution of a single mating type, MAT1-2 (79%). These results are similar to those of Kusai et al (2016), observed on E. rostratum isolates from rice in Malaysia. The linkage disequilibrium and homoplasy tests did not reject the hypothesis of recombination within the E. rostratum populations of Burkina Faso.…”
Section: Rodolfisupporting
confidence: 91%
“…Identification of mating types was done by amplification of MAT1-1 and MAT1-2 genes with primers specific to B. oryzae (Ahmadpour et al, 2018) and E. rostratum (Kusai et al, 2016). Each PCR reaction using the kit Go-Taq (Promega) had a final volume of 25 mL, containing 1 mL of template genomic DNA (20 ng/µL),1 mL forward primer (10 µM), 1 mL reverse primer (10 µM), 1µL of dNTPs (10 µM each), 5 mL of the buffer 5x, 0.25 µL Taq polymerase (5U/µL) and 14.75 mL sterile water.…”
Section: Mating Type Characterization and In Vitro Sexual Reproductionmentioning
confidence: 99%
“…It was reported that Phoma sp causes leaf spot disease on Schisandra chinensis in Korea (Choi, 2014). Setosphaeria rostrata is a common plant pathogen causing leaf spot disease, affects a wide range of plant species, mainly grasses (Kusai et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Exserohilum has been described as a pathogen on cereals and grasses (Kusai et al 2016). Every year about 10-20% losses due to diseases are reported in wheat (Figueroa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Exserohilum pathogenic species include E. pedicellatum, E. prolatum producing leaf spot on maize and wheat, but E. rostratum infect numerious hosts, including wheat, banana, maize and grasses (Lin et al 2011). Exserohilum leaf blight is characterized by leaf and stem lesions that spread to the entire leaf after a few days of infection (Kusai et al 2016). A strong interaction between the pathogen and the environment is also reported (Kusai et al 2016).…”
Section: Introductionmentioning
confidence: 99%